What are the Unmet Needs and Most Relevant Treatment Outcomes According to Patients with Inflammatory Bowel Disease? A Qualitative Patient Preference Study. (27th September 2022) - Schoefs, Elise; Vermeire, Séverine; Ferrante, Marc; Sabino, João; Lambrechts, Tessy; Avedano, Luisa; Haaf, Isabella; De Rocchis, Maria Stella; Broggi, Andrea; Sajak-Szczerba, Magdalena; Saldaña, Roberto; Janssens, Rosanne; et al.
Abstract: Background and Aims: As more therapeutic options with their own characteristics become available for inflammatory bowel disease [IBD], drug development and individual treatment decision-making needs to be tailored towards patients' preferences and needs. This study aimed to understand patient preferences among IBD patients, and their most important treatment outcomes and unmet needs. Methods: This qualitative study consisted of [1] a scoping literature review, [2] two focus group discussions [FGDs] with IBD patients [ n = 11] using the nominal group technique, and [3] two expert panel discussions. Results: IBD patients discussed a multitude of unmet needs regarding their symptoms, side-effects, and psychological and social issues for which they would welcome improved outcomes. In particular, IBD patients elaborated on the uncertainties and fears they experienced regarding the possible need for surgery or an ostomy, the effectiveness and onset of action of their medication, and the medication's long-term effects. Furthermore, participants extensively discussed the mental impact of IBD and their need for more psychological guidance, support, and improved information and communication with healthcare workers regarding their disease and emotional wellbeing. The following five characteristics were identified during the attribute grading as most important: prevent surgery, long-term clinical remission, improved quality of life [QoL], occurrence of urgency and improved labour rate. Conclusions: This study suggests that IBD drug development and treatment decision-making are needed to improve IBD symptoms and adverse events that significantly impact IBD patients' QoL. Furthermore, this study underlines patients' need for a shared decision-making process in which their desired treatment outcomes and uncertainties are explicitly discussed and considered.